If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + -37 = 2(u + 1) Reorder the terms: -37 + 5u = 2(u + 1) Reorder the terms: -37 + 5u = 2(1 + u) -37 + 5u = (1 * 2 + u * 2) -37 + 5u = (2 + 2u) Solving -37 + 5u = 2 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. -37 + 5u + -2u = 2 + 2u + -2u Combine like terms: 5u + -2u = 3u -37 + 3u = 2 + 2u + -2u Combine like terms: 2u + -2u = 0 -37 + 3u = 2 + 0 -37 + 3u = 2 Add '37' to each side of the equation. -37 + 37 + 3u = 2 + 37 Combine like terms: -37 + 37 = 0 0 + 3u = 2 + 37 3u = 2 + 37 Combine like terms: 2 + 37 = 39 3u = 39 Divide each side by '3'. u = 13 Simplifying u = 13
| 90+x+(2x+21)= | | 2+y+3=0 | | -1-8b=-8-9b | | -3y+(6*2)=-6 | | 9y+27=-3x | | -2=-6x+4 | | 8=x-2/7 | | -2p+3=-12 | | 2y+(4*2)=12 | | 3y+5=2(x+1) | | 3x-(9x+7)=4x-27 | | y-(8*2)=-6 | | (5x+2)= | | -6t-7=-1-7t-10 | | x^3+2x^2-11x+52=0 | | 3m+4=-3 | | y+(3*2)=12 | | -5x+4=2x+16 | | 19-f=46 | | M^2=160 | | -6+7=-1-7t-10 | | (4x-10.7)=(2x+6.3) | | 23+15= | | (4x-10.7)= | | 1/2b-19/6=1/3b+5/6 | | 12y=2x+1 | | 12y=8x+3 | | x^2-4x=2u+35 | | 4(w-2)-8=-3(-6w+6)-8w | | k+6k= | | (2x)+(x)+(x+20)= | | 24+c=13 |